Pengaruh Beban Pajak Tangguhan, Leverage, dan Manajemen Laba Terhadap Penghindaran Pajak dengan Moderasi Komisaris Independen pada Perusahaan Properti dan Real Estate yang Terdaftar di BEI Periode 2021-2024 - Adrian, Muhammad; Suhendah, Rousilita (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to examine the influence of deferred tax expense, leverage, and earnings management on tax avoidance, with independent commissioners as a moderating variable. The research focuses on property and real estate companies listed on the Indonesia Stock Exchange during the 2021–2024 period. Using the purposive sampling method, a sample of 31 companies was obtained, totaling 124 observations. Data analysis was conducted using panel data regression with the Random Effect Model (REM), processed through EViews 12 software. The results indicate that leverage has a significant positive effect on tax avoidance, while earnings management has a significant negative effect. Meanwhile, deferred tax expense has no effect on tax avoidance. Regarding the moderating role, the test results show that independent commissioners are unable to moderate the influence of deferred tax expense, leverage, or earnings management on tax avoidance. This suggests that the internal oversight function through the proportion of independent commissioners has not yet provided a significant impact on corporate tax policies in this sector.